Islamic Values-Based Psychoeducation for Bullying Prevention: Strengthening Students’ Mental Health and Moral Character at Pusat Asasi Darul Ulum (PADU), Kedah, Malaysia - Afiifah Dzakiyyah; Afiqa Andhina; Nadia Izzaty; Raudah Raudah; Dani Yoselisa; Fadriati Fadriati; Abu Bakar (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2026)
Bullying among students is a persistent concern that can adversely affect adolescents’ mental health, social relationships, and academic development, including in Islamic educational settings. In Malaysia, bullying among secondary school students takes various forms, including verbal, physical, psychological, and cyberbullying, with potential consequences such as anxiety, depression, and declining academic performance. As an Islamic pre-university institution, Pusat Asasi Darul Ulum (PADU) Kedah requires preventive approaches that address bullying while simultaneously strengthening students’ moral character and psychological resilience. This community engagement program aimed to implement Islamic values-based psychoeducation to enhance students’ understanding of bullying, develop practical prevention skills, and strengthen psychologically and spiritually grounded resilience. The program involved approximately 60 PADU students and employed an interactive approach combining peer education, Islamic values integration, theoretical sessions, group discussions, case-based activities, and interactive games. The results indicated that participants developed a broader understanding of bullying, including its verbal, physical, psychological, and cyber forms, and demonstrated greater awareness of its potential impact on mental health and strategies for prevention and reporting. Interactive discussions also provided a supportive space for participants to express their perspectives and experiences and fostered a collective commitment to preventing bullying. Overall, the program contributed to strengthening students’ awareness, empathy, moral responsibility, and commitment to creating a respectful and psychologically safer learning environment. The program may be sustained through integration into character education, teacher training, and institutional anti-bullying initiatives.